Design, Synthesis and Biological Activity Evaluation of β-Carboline Derivatives Containing Nitrogen Heterocycles - Wu, Guiyun; Wang, Wenhang; Li, Fulian; Xu, Chenlu; Zhou, Yue; Li, Zhurui; Liu, Bingqian; Shao, Lihui; Chen, Danping; Bai, Song; Wang, Zhenchao (Molecules (Basel, Switzerland), 2024)
A series of β-carboline derivatives containing nitrogen heterocycles were designed and synthesized. All compounds were screened for their antitumor activity against four human tumor cell lines (A549, K562, PC-3, T47D). Notably, compound N-(4-(morpholinomethyl)phenyl)-2-((5-(1-(3,4,5-trimethoxyphenyl)-9H-pyrido[3,4-b]indol-3-yl)-1,3,4-oxadiazol-2-yl)thio)acetamide (8q) exhibited significant inhibitory activity against PC-3 cells with an IC50 value of 9.86 µM. Importantly, compound 8q effectively suppressed both the proliferation and migration of PC-3 cells. Mechanistic studies revealed that compound 8q induced cell apoptosis and caused the accumulation of reactive oxygen species (ROS), leading to cell cycle arrest in the G0/G1 phase in PC-3 cells.